2018
DOI: 10.1186/s13071-018-2828-2
|View full text |Cite
|
Sign up to set email alerts
|

A forecasting model for dengue incidence in the District of Gampaha, Sri Lanka

Abstract: BackgroundDengue is one of the major health problems in Sri Lanka causing an enormous social and economic burden to the country. An accurate early warning system can enhance the efficiency of preventive measures. The aim of the study was to develop and validate a simple accurate forecasting model for the District of Gampaha, Sri Lanka. Three time-series regression models were developed using monthly rainfall, rainy days, temperature, humidity, wind speed and retrospective dengue incidences over the period Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…At present, this method has been widely used in the prediction of infectious diseases, and has achieved successful prediction results, for instance, Tian C W et al [4] forecasted monthly cases of hand-foot-mouth disease successfully in China; Wang T et al [5] suggested that ARIMA(3,1,1)(2,1,1) 12 model was reliable with a high validity, which could be used to predict hemorrhagic fever with renal syndrome incidence in Zibo; Myriam Gharbil et al [6] predicted the dengue incidence in Guadeloupe based on time series analysis; López-Montenegro LE [7] predicted dengue cases in Colombia from 2018 to 2022 based on Auto-Regressive Integrated Moving Average (ARIMA) model; Zheng Y-L et al [8] and Liao Z [9] forcasted TB incidence successfully using SARIMA model, etc. [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…At present, this method has been widely used in the prediction of infectious diseases, and has achieved successful prediction results, for instance, Tian C W et al [4] forecasted monthly cases of hand-foot-mouth disease successfully in China; Wang T et al [5] suggested that ARIMA(3,1,1)(2,1,1) 12 model was reliable with a high validity, which could be used to predict hemorrhagic fever with renal syndrome incidence in Zibo; Myriam Gharbil et al [6] predicted the dengue incidence in Guadeloupe based on time series analysis; López-Montenegro LE [7] predicted dengue cases in Colombia from 2018 to 2022 based on Auto-Regressive Integrated Moving Average (ARIMA) model; Zheng Y-L et al [8] and Liao Z [9] forcasted TB incidence successfully using SARIMA model, etc. [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in these variables affect the population dynamics of mosquito vectors and the consequent risk of dengue transmission [ 14 ]. Increased precipitation during the monsoon season facilitates vector population growth by providing aquatic media for mosquitoes, although excessive rainfall can lead to flushing out of breeding sites and killing of mosquito larva [ 15 , 16 ]. In some urban regions, stable larval habitats are provided by large domestic water tanks that are used to manage periodic water shortages [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite many efforts, in 2017, Sri Lanka experienced the most severe dengue outbreak with 186,101 infections island wide with over 250 dengue-related deaths [3]. Every year, nearly half of the incidences are reported from the Western Province which comprises Districts of Colombo, Gampaha, and Kalutara, and despite many efforts, the second highest number of dengue cases is reported from the District of Gampaha since 2010 [4][5][6]. Further, during the dengue epidemic in July 2017, the highest number of dengue cases was reported from the District of Gampaha [7].…”
Section: Introductionmentioning
confidence: 99%